Crystal Schuller: capstone - Schuller, Crystal, artist (Colorado State University. Libraries, 2014)
The artist's statement: The creation of these pieces has been a journey in understanding the use of negative space, color and imagery to emphasize content and type choices. The result is a pervasive theme of minimalism that manifests through color palettes, composition, and imagery. The color choices made throughout are intended to set strong themes for each project and limit visual clutter. Within the pieces emerges a theme of interplay between organic, free-form design elements and rectilinear geometry. To achieve this, emphasis is placed primarily on typography and composition, with texture and curvilinear components being used secondarily to support each design. Projects span an array of intents, including publication, corporate identity, public awareness, and package design.
Colorado State University Art Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.